Effects of strain rate and bond preparation for dissimilar materials in energy dispersive applications - Commins, T; Siviour, CR (EDP Sciences, 2021)
Composite materials, typically consisting of two or more dissimilar materials adhered together in layers, are frequently used for energy absorption applications. The interface and material characteristics strongly influence the global energy absorptive capability of the composite. This research focuses on ceramic-polymer interfaces and, in particular, links between the properties of the composite, the interface and the separate materials. After characterisation of the materials, the effects of impact speed and bond condition were considered for a polymer-ceramic bond in a threepoint bend configuration. Specimens were loaded in a screw-driven machine at 0.05 mm s-1 and through projectile impact at speeds of approximately 50 m s-1. Screw-driven experiments were performed at ambient and sub ambient conditions, with the temperature chosen to simulate the expected polymer performance in the gas gun experiment, making use of the equivalence of rate and temperature for polymers.